Eddy-covariance flux measurements in an Italian deciduous forest using PTR-ToF-MS, PTR-QMS and FIS. Issue 8 (21st June 2018) - Jensen, Niels Roland; Gruening, Carsten; Goded, Ignacio; Müller, Markus; Hjorth, Jens; Wisthaler, Armin
ABSTRACT: A field campaign in a deciduous forest in Ispra, Italy, was performed by the Joint Research Centre, Ispra, Italy, together with University of Innsbruck, Austria, in 2013, using PTR-ToF-MS (proton transfer reaction – time-of-flight – mass spectrometry), PTR-QMS (proton transfer reaction – quadrupole mass spectrometry), FIS (fast isoprene sensor) and other instrumentations. The main purpose of the campaign was to measure volatile organic carbon (VOC). One of the outcomes of this investigation was the comparison between the three VOC measurement techniques, focusing on the VOC-flux values that could be measured, VOC-volume-mixing-ratio (VOC-VMR) values that could be measured, the number of VOCs identified/measured, and finally if any oxidation products from the primary emitted VOC could be identified/measured. To the best of our knowledge, it is the first time that these three techniques have been used simultaneously during a campaign in a forest, and the comparison of the three techniques is presented in details (PTR-ToF-MS, PTR-QMS and FIS). It was concluded that the isoprene data generated by the three instruments were in good agreement. With PTR-ToF-MS, the following main results were achieved during the summer campaign 2013: The VMR of isoprene was measured up to 16 ppb; large fluxes of isoprene with values up to 53 nmol m −2  s −1 by PTR-ToF-MS; mean diurnal (24 h) averages of VMR of isoprene of (1.07 ± 0.53) ppb and mean diurnal (24 h) flux of isoprene of (5.20 ± 2.42) nmol m −2  s −1 . For the isoprene oxidation products methyl-vinyl-ketone/methacrolein (MVK/MACR), VMRs of (0.42 ± 0.22) ppb were measured as a mean diurnal (24 h) average. Mean diurnal (24 h) flux of MVK/MACR were measured to be (0.06 ± 0.04) nmol m −2  s −1 ; for the monoterpenes, the VMR was measured to be (0.10 ± 0.09) ppb mean diurnal (24 h) and mean diurnal (24 h) flux of monoterpenes to be (0.08 ± 0.05) nmol m −2  s −1 . Detailed descriptions of the fluxes/VMRs of other VOCs, acetone/methanol/acetaldehyde, are also presented. The results obtained here have also been compared to several other similar studies and campaigns.